THE FARMING AND MARKETING OF ORGANIC LETTUCE: STUDY AT BOBOSAN VILLAGE, KEDUNGBANTENG SUB-DISTRICT, BANYUMAS - irine Kartika Eka Wijayanti; Indah Widyarin; Ratna Satriani (Agros Journal of Agriculture Science, 2017)
Banyumas has great potential as a producer of organic lettuce in term of condition of natural, human resources and availability of market. The centre producer of organic lettuce is located in district of Kedungbanteng, and managed by farmers group "abdi tani". The aim of this study is to analyze: 1). The cost and income farming of organic lettuce; 2). Financial feasibility of organic lettuce farm; 3). The channel and structure of organic lettuce market. Processing and data analysis performed qualitatively and quantitatively. The data used is to the production and marketing of organic lettuce in period of June-July 2016. Quantitative analysis performed using analysis of cost, farm income, and R/C. Qualitative analysis was conducted to determine the channel and structure of organic lettuce market. The results showed that organic lettuce farm income generating positive value and the value of R/C is greater than one (R/C >1), the farming is profitable and feasible. Organic lettuce marketing channels through the use of one channel, such farmers, traders, retailers (supermarket). Farmers faced monopsony market structure, while traders and retailers deal with oligopoly one.